Модифікування властивостей кремнієвих функціональних пористих матеріалів для фотоелектричних перетворювачів - Єрохов, Валерій Юрійович (Національний університет "Львівська політехніка", 2013)
Дисертація присвячена розробленню та вдосконаленню технології отримання кремнієвих фотоелектричних перетворювачів сонячної енергії з використанням шарів функціонального пористого кремнію, що забезпечує одночасне підвищення ефективності перетворення та спрощення технології їх виготовлення. Розроблена технологія формування нано-, мікро- і макротекстур моно- і мультикристалічних кремнієвих підкладок фотоелектричних перетворювачів, шляхом модифікування електрохімічної технології отримання пористого кремнію, що полягає в комплексному застосуванні розчинів-травників на основі фтористоводневої кислоти з додаванням ((СН3)2NСОН) одночасно з функціональними складниками (C2H5OH, (СН3)СООН, H2O, СН3ОН, C2H6O2), що дозволяє отримати набір текстур (краплеподібної та колоноподібної форми) кремнієвих фотоелектричних перетворювачів із ефективністю перетворення 16,4% при АМ 1,5. Розроблено нову електрохімічну технологію створення багатошарового мультипористого антивідбивного покриття типу “Black Si” на основі пористого кремнію. Встановлені закономірності технології отримання текстур типу “Honeycomb” методом хімічного травлення, при тому нові травники на основі розчину фтористоводневої і азотної кислот (HF:HNO3=1:2) з інгибіторами поверхневих реакцій (C3H8O3 чи C2H6O2) та органічних сполук з функціональними амідними групами ((СН3)2NСОН) з добавленням складників (C6H6, C3H6O) дозволяють підвищити ККД сонячних елементів з текстурою типу “Honeycomb” в 1,26 раз. Розроблений метод отримання пористого кремнію модифікованим хімічним багатостадійним травленням і визначено, що використання такої технології забезпечує підвищення ККД ФЕП на основі мультикристалічних підкладок кремнію Baysix до 18% при АМ 1,5. Диссертация посвящена разработке и совершенствованию технологии получения кремниевых фотоэлектрических преобразователей солнечной энергии с использованием слоев функционального пористого кремния, что обеспечивает одновременное повышение эффективности преобразования и упрощение технологии их изготовления. Разработана технология формирования нано-, микро- и макротекстуры моно- и мультикристаллических кремниевых подложек фотоэлектрических преобразователей, путем модифицирования электрохимической технологии получения пористого кремния, которая заключается в комплексном применении растворов-травителей на основе плавиковой кислоты с добавлением ((СН3)2NСОН) одновременно с функциональными частями (C2H5OH, (СН3)СООН, H2O, СН3ОН, C2H6O2), что позволяет получить набор текстур (каплевидной и колоннообразной формы) кремниевых фотоэлектрических преобразователей с эффективностью преобразования 16,4% при АМ 1,5. Разработана новая электрохимическая технология получения многослойного мультипористого антиотражающего покрытия типа "Black Si" на основе пористого кремния. Установлены закономерности технологии получения текстур типа "Honeycomb" методом химического травления, при том новые травители на основе плавиковой и азотной кислот (HF:HNO3=1:2) с ингибиторами поверхностных реакций (C3H8O3 или C2H6O2) и органических соединений с функциональными амидными группами ((СН3)2NСОН) с добавлением компонентов (C6H6, C3H6O) позволяют повысить КПД солнечных элементов с текстурой типа "Honeycomb" в 1,26 раз. Разработан метод получения пористого кремния модифицированным химическим многоэтапным травлением и определено, что использование такой технологии обеспечивает повышение КПД ФЭП на основе мультикристаллических подложек кремния Baysix до 18% при АМ 1,5. The current scientific and applied task of developing and improving the technology of silicon solar cells using functional porous silicon layer that provides simultaneous increase efficiency and simplify their production technology is solved in the thesis. Based on a complex study of the properties of porous silicon layers a technology of micro- and macrotexture of mono- and multicrystalline silicon photovoltaic substrates by electrochemical modification technology of porous siliconi is developed. It is an integrated application of solutions, etchants based on hydrofluoric acid with the addition of ((CH3)2NCOH) simultaneously with functional components (C2H5OH, (CH3)COOH, H2O, CH3OH, C2H6O2). It is shown that using permanently-periodical current density sets allowes to control the porosity (40...90%) with thickness (10 nm ... 35 μm) and refractive index (1,2...3,25) of porous silicon layers. It provides to get a set of silicon photovoltaic cells (columnar and teardrop-shaped) textures with a 16.4% efficiency under AM 1,5 in the wavelength range 400 ÷ 1000 nm. The elemental analysis of the silicon multicrystalline substrates surface Baysix type was realised by the secondary ions mass spectroscopy used at different technological stages of porous silicon formation. It allowed to compare a clear surface before etching and the surface after the etching in the electrolyte based on hydrofluoric acid as well as after hydrogenation both at secondary ions specra and at 2D images of elements distribution along the surface (ion microprobe mode and mass-spectroscopy ion microscope mode). As it is evident from the secondary ions mass spectra of the silicon surface before the etching the oxygen clusters as well hydrogen links are presented on the surface. After the etching the spectrum appeared to have energetic peaks corresponding to the ions СН3+. The hydrogen concentration definded using the secondary ions H2+ intensity is larger at the surface and shows a steadily decreasing deep into the sample. Based on studies of structural features of silicon substrates was developed a new electrochemical technology of porous silicon by stepped reduction in the current density and an increase in the duration of the electrochemical process for each layer creating a multiporous multilayer antireflective coating such as "Black Si". This enabled us to increase the number of layers in a multilayer antireflective coating from 2…4 to 10...20 or more. It was found that an effective tool for influencing the functionality and nanoporous of silicon substrate surface textures for solar cells is the use of chemical etching of the surface. The next step is to fill of the newly created texture by silicon organic adsorbent created by the sol-gel technology. The technology of "Honeycomb" type textures is modified by chemical etching on the solar cells silicon substrates surface. Dependences of the etching rate on the proportion of the etchant, permittivity and values of surface tension of organic components were determined. New etchants based solutions of hydrofluoric and nitric acids (HF:HNO3=1:2) of the inhibitor surface reactions (C3H8O3 or C2H6O2) and organic compounds with amide functional groups ((CH3)2NCOH) with added ingredients (C6H6, C3H6O) were developed. The texture, obtained by this method, allowes to reduce optical losses caused by the integral index reflection from the silicon substrates surface from 37% to 11,5% at AM 1,5 in the spectral range 400…1000 nm. The method for porous silicon obtaining by the modified multistage chemical etching was developed. It was determined that the use of such technology increases the efficiency of solar cells based on Baysix multicrystalline silicon substrates to 18% at AM 1,5.
Модифицирование свойств кремниевых функциональных пористых материалов для фотоэлектрических преобразователей
The modification of the functional properties of porous silicon materials for photoelectric converter
Keywords: електрохімічне анодування; кремній; сонячний елемент; пористий кремній; хімічне травлення; фотоелектричний перетворювач; антивідбивне покриття; багатошарове покриття; электрохимическое анодирование; кремний; солнечный элемент; пористый кремний; химическое травление; фотоэлектрический преобразователь; антиотражающее покрытие; многослойное покрытие; electrochemical anodization; silicon; solar cell; porous silicon; chemical etching; photoelectric converter; anti-reflective coating; multi-layer coating